Regioselective Synthesis of the FXR Antagonist E-Guggulsterone from Three Natural Steroids - Chin, Jungwook; Hahn, Dongyup; Won, Dong Hwan; Cho, Sung Jin; Kim, Kyung-Hee; Ham, Jungyeob; Kang, Heonjoong (대한화학회, 2017)
In our attempt to develop a method to synthesize E- and Z-guggulsterones [antagonists of farnesoid X receptor (FXR)], we have succeeded in synthesizing E-guggulsterone selectively from three steroids, viz, 4-androsten-3, 17-dione (2), 5-androsten-3 beta-ol-17-one (DHEA) (3), and testosterone (4), in 68, 86 and 62% overall yield, respectively. We also investigated the biological effects of the synthetic E- and Z-guggulsterones and found that E-guggulsterone was more potent than Z-guggulsterone in inhibiting FXR transactivation